The Efl students' perspectives on the usefulness of ict-based learning - Amrullah, Amrullah; Lail, Husnul; Sumayani, Sofia Rahmi (Journal of Language and Pragmatics Studies, 2023)
Teaching and learning activities have been associated with the use of Information and Communication Technology (ICT). In the context of English language learning, ICT is a resource and tool for supporting students in their learning process. With the use of different English learning activities, ICT offers students a range of sources to obtain authentic content and improve their language abilities. This research aims to analyze the students’ perspectives on the use of ICT-based learning in their learning activities. This study used quantitative descriptive study. The sample of this research was 31 students of the 8th semester students’ English department University of Mataram academic year 2021/2022. The data were collected by using an online questionnaire, an interview, and documentation. The process analyzation was using SPSS, then Spearman's Rho test applied to determine how closely the two variables are related. The result indicated that the students have a positive perspective on the use of ICT-based learning contributed to their learning process. Overall data of mean score 3.95 (SD 0.563) on the students’ perspectives on implementing ICT-based learning show a positive impact. The findings are also revealed that there is a significant correlation between the two variables and a positive correlation coefficient (0.665). Thus, it can be concluded that the better ICT quality improves, the better the quality of students' English learning it would be.